TINGKAT KELANGSUNGAN HIDUP BENIH IKAN NILA GIFT (Oreochromis niloticus) PADA SALINITAS YANG BERBEDA - Adria Yulan; Ida A. Anrosana P.; Ariesia A. Gemaputri (Universitas Gadjah Mada, 2013)
Oreochromis niloticus is an eurihaline ﬁ sh which has good adaptation level of salinity. Increasing demand of Oreochromis niloticus and availability of salty water in Indonesia give opportunity to develop new strain which is more suitable. The aim of this research is to know the effect of different salinity to Oreochromis niloticus juvenile survival rate and different salinity that can be tolerated. Mean date of all parameters evaluated were sudjected to an analysis of variance (ANOVA). When signiﬁ cant differences were found the means were tested by BNT at level of signiﬁ cant 1%.The result shows that salinity range 10 to 15 ppt can be tolerated by Oreochromis niloticus with survival rate level of 87,5 % to 81,25 % and 20 to 25 ppt give bad effect toward the survival rate level 25 % to 0 %.